Private data access control model based on block chain technology in the internet of things environment - Weijin JIANG; Tiantian LUO; Ying YANG; En LI; Wenying ZHOU (物联网学报)
The traditional “centralized” access control technology can no longer guarantee the security of private data access control in the current internet of things environment.Based on the ABAC (attribute-based access control) model, a blockchain based access control framework for the internet of things and a private data access control model were proposed.Firstly, the basic framework and process of access control were described and analyzed in detail, and an auditable access control model was proposed to systematically manage the access control policies of private data through the requests, responses and access records stored in the blockchain network.Then, an auditable access control system based on blockchain technology was proposed, which can provide distributed, fine-grained and dynamic access control management in the internet of things, realize the effective management and auditable access to data, and adopt the access control method based on smart contract to realize the transparent, traceable and automatic access control over the internet of things resources.Finally, simulation experiments and performance tests verify the effectiveness and security of the access control model and system.